2017
DOI: 10.1038/bcj.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of TET activity with ascorbic acid induces epigenetic modulation of lymphoma cells

Abstract: The Ten Eleven Translocation (TET) enzymes have been found to be mutated in both diffuse large B-cell (DLBCL) and peripheral T-cell (PTCL) lymphomas resulting in DNA hypermethylation. Recent studies in embryonal stem cells showed that ascorbic acid (AA) is a cofactor for TET with a binding site at the catalytic domain, and enhances TET activity. We hypothesized that AA could potentially enhance TET activity in lymphoma cells to cause DNA demethylation, reactivate expression of tumor suppressor genes and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 39 publications
2
41
0
3
Order By: Relevance
“…Cells were cul-to culture media does not play a role in the DNA demethylation and increase in hydroxymethylation in ccRCC with AA treatment and that this effect is TET enzyme dependent (both via catalase control and TET-knockdown experiments). This is an important consideration, since hydrogen peroxide is responsible for the acute cytotoxicity of cancer cells with short-term exposure to AA, as demonstrated in this study and others (16,17,31) with the complete reversal of short-term exposure cytotoxicity with catalase. However, despite the multiple in vitro studies demonstrating AA-induced H 2 O 2 -mediated cancer cytotoxicity and in vivo data demonstrating that H 2 O 2 is produced in the extracellular fluid with high-dose parenteral AA, it remains a matter of debate whether H 2 O 2 plays a significant role in AA-induced cytotoxicity in patients.…”
Section: Methodssupporting
confidence: 61%
“…Cells were cul-to culture media does not play a role in the DNA demethylation and increase in hydroxymethylation in ccRCC with AA treatment and that this effect is TET enzyme dependent (both via catalase control and TET-knockdown experiments). This is an important consideration, since hydrogen peroxide is responsible for the acute cytotoxicity of cancer cells with short-term exposure to AA, as demonstrated in this study and others (16,17,31) with the complete reversal of short-term exposure cytotoxicity with catalase. However, despite the multiple in vitro studies demonstrating AA-induced H 2 O 2 -mediated cancer cytotoxicity and in vivo data demonstrating that H 2 O 2 is produced in the extracellular fluid with high-dose parenteral AA, it remains a matter of debate whether H 2 O 2 plays a significant role in AA-induced cytotoxicity in patients.…”
Section: Methodssupporting
confidence: 61%
“…Particularly, a recent study showed that vitamin C can block the serial re-plating capacity of haematopoietic stem and progenitor cells (HSPCs) when catalase, an enzyme that can decompose H 2 O 2 to water and oxygen, was included with vitamin C in the media [30]. Consistent with this, vitamin C can also cause epigenetic effects in lymphoma cell lines, which is independent of H 2 O 2 [10,31]. Collectively, vitamin C may have dual effects on neoplastic cells, including differentiation induction upon lowdose prolonged exposure and cytotoxicity at high doses.…”
Section: Discussionmentioning
confidence: 84%
“…A drawback of in vitro studies is that they do not take into account the tumour microenvironment, such as the presence of oxygen and iron, which can interfere with the potential therapeutic efficacy of vitamin C in vivo. Additionally, the production of reactive oxygen species (ROS) via oxidation of vitamin C appears to be a major underlying event, leading to the selective killing of cancer cells [10]. Thus, we also used APM, which is an oxidation-resistant vitamin C derivative [11], to evaluate whether the effect of vitamin C is dependent on ROS.…”
Section: Introductionmentioning
confidence: 99%
“…VitC is a known cofactor for several Fe 2+ and α-ketoglutarate-dependent dioxygenases, including enzymes regulating histone and DNA methylation, such as ten-eleven translocation (TET) DNA hydroxylases. Indeed, it has been reported that VitC can act as an epigenetic remodeling agent on cancer cells [39,40], as well as on several non-neoplastic cell types, including immune cells [41,42]. The experimental models used in this work (cells, organoids, human tumors transplanted in immunocompromised animals) were not suited to assess the potential effect of VitC on modulating anticancer immune responses [43,44].…”
Section: Discussionmentioning
confidence: 96%